Understanding Dynamics of Strategic Decision Making in Venture Creation: A Process Study of Effectuation and Causation - Reymen, Isabelle M.M.J.; Andries, Petra; Berends, Hans; Mauer, Rene; Stephan, Ute; van Burg, Elco (Strategic Entrepreneurship Journal, 2015)
This study draws upon effectuation and causation as examples of planning‐based and flexible decision‐making logics and investigates dynamics in the use of both logics. The study applies a longitudinal process research approach to investigate strategic decision making in new venture creation over time. Combining qualitative and quantitative methods, we analyze 385 decision events across nine technology‐based ventures. Our observations suggest a hybrid perspective on strategic decision making, demonstrating how effectuation and causation logics are combined and how entrepreneurs' emphasis on these logics shifts and re‐shifts over time. We induce a dynamic model that extends the literature on strategic decision making in venture creation. Copyright © 2015 Strategic Management Society.